Footwear characteristics in people with inflammatory arthritis in Singapore. Issue 1 (December 2016) - Carter, K.; Lahiri, M.; Cheung, P.; Santosa, A.; Rome, K.
Abstract Background Foot problems are common in people with inflammatory arthritis. Despite suitable footwear having the potential to alleviate pain, improve mobility and maintain independence, previous studies have found many people with inflammatory arthritis wearing poorly fitting and inappropriate footwear. Footwear styles and characteristics have not been reported in a Singapore inflammatory arthritis population. The objective of this study was to identify current footwear styles and characteristics of footwear worn by people with inflammatory arthritis in Singapore. Methods One-hundred-and-one participants with inflammatory arthritis were recruited from the rheumatology outpatient clinic of a large public hospital in Singapore. Disease and clinical characteristics were recorded. A patient-reported outcome included current foot pain. An objective footwear assessment of style, age of shoe, fit and construction was conducted. Results The majority of participants were Chinese women with a mean (SD) age was 52.0 (15.0) years old and a mean (SD) disease duration of 9.3 (0.3) years. We found 50 % of participants (n  = 51) reported footwear problems. Sandals (n  = 27, 26 %), flip-flops (n  = 19, 19 %) and moccasin type (n  = 19, 19 %) was the most common footwear choice. Evaluation of footwear characteristics found that there was a lack of motion control features. Only 32 (32 %) participants had correctly fitting footwear with regard to length, width and depth. No participant was wearing therapeutic footwear. Conclusion This study provides the first insight into footwear preferences of people with inflammatory arthritis in Singapore. Use of slip-on and poorly fitting footwear was found to be common in people with inflammatory arthritis. Further research on footwear preferences in Southeast-Asian communities needs to take into account cultural habit and preference, socio-economic status, footwear options and affordability.